Modulation of oxygen vacancies assisted ferroelectric and photovoltaic properties of (Nd, V) co-doped BiFeO3 thin films. (14th June 2018) - Agarwal, Radhe; Sharma, Yogesh; Hong, Seungbum; Katiyar, Ram S
Abstract: We are reporting on the improved ferroelectric and photovoltaic properties of (Nd 3+, V 5+ ) co-doped (Bi0.95 Nd0.05 )(Fe1− x V x )O3 (BNFVO) ( x   =  0.01, 0.03) thin films grown by PLD. BNFVO thin films showed reduced leakage current, lower optical bandgap, and improved ferroelectricity compared to BFO films, which can be explained by valance change and extinguishing oxygen vacancies due to the doping effect. Piezoresponse force microscopy measurements showed an improved domain back switching in doped thin films indicating that the suppression of oxygen vacancies offset the effect of polarization flipping caused by doping. Further, we found a relatively stable and enhanced photovoltaic effect in BNFVO films with an order of magnitude higher photocurrent and almost doubled photovoltage in comparison to BFO films, which can be explained by less recombination between hopping electrons and oxygen vacancies. Our results demonstrate the significance of dopant selection to suppress the oxygen vacancies for improved ferroelectric and photovoltaic properties of BFO films.